A Comparative Study of Different Carriers for Bioinoculant Preparation - Bhatia, Pallavi; Harsh, N. S. K.; Dubey, R. C.; Kaushik, P. K. (Indian Forester, 2017)
Biological control is most applicable method for controlling plant diseases. The term applies the use of microbial antagonist to suppress disease as well as specific pathogen. For controlling the disease, biocontrol agent must be ecologically fit to survive, become well established and function within the particular conditions of the ecosystem. In general, organism introduced into an established system does not persist for a long time. The introducing agent must have an acceptable shelf life. Major considerations in developing a viable biocontrol product are the production, formulation and delivery of propagules that are viable and effective. Five solid carriers viz., groundnut shell, saw dust, bagasse, paddy straw and soil were used for the preparation of carrier based inoculums ofÂ TrichodermaÂ andÂ RhizobiumÂ species screened previously against wilt disease pathogenÂ Fusarium solani. Physical properties of the carriers were also measured which were found optimum for inoculum growth. Bagasse and saw dust was proved best among all the five carriers by maintaining high population density of inoculants among the year. Groundnut shell and paddy straw was considered as moderate carriers in comparison to bagasse and saw dust while soil was unable to maintain appropriate viable cells of the inoculants all over the year.